Intercultural communication in the process of establishing the foundations of ukrainian national identity - Mykhailo Yurii (Науковий вісник Чернівецького національного університету імені Юрія Федьковича. Історія, 2022)
The article deals with the picture of the world, the linguistic picture of the world, the Ukrainian language, thanks to which the Ukrainian national identity is represented. It is noted that the picture of the world is a set of worldview knowledge about the world, which is formed in the process of evaluation by the subject of the results of knowledge of the surrounding reality. The subject forms a picture of the world for himself, based on his own feeling, perception, representation of forms of thinking and self-awareness. And this picture of the world cannot but be reflected with the help of a linguistic picture of the world, in which, in its turn, the national language picture will show through. The linguistic picture of the world is historically formed in the everyday knowledge of the community and the set of ideas about the world reflected in the language, in a certain way of reflecting and constitutionalizing reality through the prism of cultural and national features inherent in a certain linguistic group, the interpretation of the surrounding world according to the national conceptual and structural canons of reflecting reality in the mind ethnicity. It is emphasized that language is the main component of culture and at the same time its tool. People’s culture is verbalized in language, and language reflects the key concepts of culture, reproducing them in words. Thus, language creates a subjective image of the objective world. The language reflects the accumulated experience of humanity; it acts as a «mental mirror» of national and cultural values. Thanks to language, a person expresses and knows himself, representing himself national identity, in this case Ukrainian. A detailed analysis of the formation of the world language picture of the Ukrainian people and its further influence on the formation of the Ukrainian nation is given.